PENENTUAN KADAR ASAM AMINO ESENSIAL (METIONIN, LEUSIN, ISOLEUSIN DAN LISIN) PADA TELUR PENYU DAN TELUR BEBEK - agita rachmala ginting; saibun sitorus; winni astuti (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2017)
Determination of amino acids essential’s content (methionine, leucine, isoleucine and lysine) on turtle eggs and duck eggs. Turtle eggs and duck eggs are a high animal protein source and easy to obtain. This research has been carried out by categorizing of turtle eggs and duck eggs by size and continued analysis of water content by Methods of Gravimetry, analyzes protein content total by the method of Kjeldahl and analysis of the levels of essential amino acids with method of HPLC (High Performance Liquid Chromatography). In this study, the researcher found the water content in the mix (large, medium and small) 75.2889% and turtle eggs on the mix 67.9020% duck egg. Total protein content in the mix turtle eggs 8.9268% and the mix duck eggs 14.2455%. Levels of essential amino acids in the mixture turtle eggs undetectable methionine, 3.25% leucine, isoleucine and lysine 1.53% 2.50%. In the mix duck eggs undetectable methionine, 1.30% leucine, isoleucine and lysine 0.58% to 0.38%.